TYPES OF ORTHOSTATIC REACTIONS AND DIASTOLIC BLOOD PRESSURE PARAMETERS IN PATIENTS WITH ARTERIAL HYPERTENSION - Garkaviy, P.A.; SaraevaА.Yu.; Yabluchansky, N.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
A dependence of diastolic arterial blood pressure (DABP) changes during the clinostasis – orthostasis transition in patients with essential arterial hypertension (AH) is studied. 154 patients with AH were surveyed (58 males and 96 females) in the age of 63±7 years. Average duration of disease was 10,4±7,8 years. 48 patients diagnosed soft AH, 55 – diagnosed mild AH, 51 – diagnosed severe AH. Depending on DABP reaction in the orthostatic test patients were divided into groups: increase of DABP – group 1 (hypertonic type), unchanged DABP – group 2 (isotonic type), decrease of DABP – group 3 (hypotonic type). Criterion of DABP increase and decrease were its corresponding changes in the magnitude not less than 5 mm.hg. During the transition from clinostasis to orthostasis DABP increased in 56,5% of patients (in 62% of males and in 53,1% of females), DABP did not change in 19,5% of patients (in 13,9% of males and in 22,9% of females), DANP decreased in 24% of patients (in 24,1% of males and in 24% of females). High frequency of hypertension and hypotension types of orthostatic reactions in patients with АH indicates on the meaningfulness of aimed analysis of these types of autonomic regulation disorders during transition processes.